Law Enforcement by The Indonesian Police against Online Gambling (Judol) in Indonesia - Tania Shapna Putri; Aidul Fitriciada Azhari (Proceeding International Conference Restructuring and Transforming Law, 2025)
The development of information technology has led to the rise of online gambling, which has become a serious threat in Indonesia. Although prohibited in the Criminal Code and the Electronic Information and Transaction Law, the practice continues to grow due to high accessibility and weak law enforcement. This study aims to analyze the effectiveness of regulations and strategies for handling online gambling to protect the public and maintain socio-economic stability. This study uses a qualitative method with a descriptive-analytical approach. Data was collected through a literature study as well as an analysis of government policies related to the prevention and enforcement of online gambling. The results show that law enforcement still faces technical challenges and regulatory weaknesses. There should be legal reform, strengthening of monitoring technology, and cross-border cooperation. In conclusion, a comprehensive approach is needed to address the negative impacts of online gambling.